Reinventing Greek electroacoustic music: from tradition to multidisciplinarity - Georgaki, Anastasia (Electroacoustic Music Studies Network (EMS 05), 2005)
Greek electroacoustic music, born in the New Music environment of the sixties and developed among fruitful and critical periods, seems to be in expansion in our days. In this article we present a brief overview of the genesis and evolution of the electroacoustic music in Greece since 1967 until today, exposing three crucial periods. In the second section we present the works, the means and aesthetics of representative composers of the most recent period (1990-2005). In the last section we focus on the pedagogical and institutional development of the Greek electroacoustic music during the last fifteen years, as well as on the diversity of styles and techniques of works presented in various events in Athens and other places in Greece. We also stress the lack of an official institute for the archiving, creation and expansion of the electroacoustic music, and the indifference of the cultural authorities to cultivate such kind of music.